Perfil epidemiológico de salud bucal (higiene oral, fluorosis dental, caries dental) y conocimientos en salud bucal en escolares de 5 a 9 años del instituto Diversificado Albert Einstein Mosquera, Cundinamarca 2020 (2020)
Introduction: The infectious processes that trigger dental caries start early in relation to preventable and avoidable etiological factors with easy to apply and low cost measures, executable from the first year of life. Objective: To establish oral health status (oral hygiene, dental fluorosis, dental caries) and oral health knowledge, in schoolchildren enrolled in grades (kindergarten-third) of the Instituto Diversificado Albert Einstein. Materials and methods: A descriptive observational cross sectional study was carried out to determine the degree of oral health in 127 schoolchildren from 5 to 9 years old, an instruction on oral health knowledge was applied, the evaluation of bacterial plaque was performed with the Silness-Loe index, the presence of caries with the COPM (sum of obturated and lost caries evaluating all stages of icdas) and COPC (sum of obturated and lost caries evaluating severe stages of icdas) index and the experience of fluorosis with Dean's index. Results: The results obtained showed poor knowledge of oral health; the prevalence of caries was 64% corresponding to 81 children, with the female sex being the most affected, the values for COPM were 28%, and for COPC it was 40%, 54% (68) children presented oral hygiene deficient, 94% (119) children presented a Grade 0 of fluorosis. Conclusion: The oral health of this group of schoolchildren is affected by a high prevalence of caries, poor oral hygiene and low knowledge of oral health.